(untitled) (Research, Society and Development, 2021)
Legal Dentistry, also known as forensic anthropology, is a dental specialty that applies all knowledge in the identification of cadavers through their records and dental arches. The purpose of the review was to analyze the literature on legal dentistry related to the identification of human bodies. An integrative literature review was developed in the Lilacs, SciELO and PubMed databases in March 2019, using the descriptors, “legal dentistry”, “dental arch” and “cadaver” individually and then the crossing with the Boolean operator AND . The inclusion criteria for the selection of the sample were articles published in Portuguese and English, available in full, between 2009 and 2020, that portrayed the theme. 18 articles were found and it was verified that the great demand for the identification of corpses by civil and criminal parties, makes dental arches as an important means of identification, mainly due to the diversity of elements to be collected. Therefore, there is a need to document all the procedures and characteristics of the patient’s dental arch made by the dentist, as these are the data that will allow a greater level of success in the correct identification of the corpse.